Ethnic and Cultural Diversity as Social Capital in the Development of the Indonesian Nation - Saiman, Saiman (Jurnal Multidisiplin Sahombu, 2024)
Ethnic and cultural diversity is a fundamental characteristic of the Indonesian nation, comprised of various tribes, regional languages, traditions, and local wisdom values. This study aims to analyze how this diversity functions as social capital in Indonesian national development. Using a descriptive qualitative approach, this study explores the role of social values such as mutual cooperation (gotong royong), tolerance, solidarity, and social cohesion, which are formed through interactions between ethnic and cultural groups. The results indicate that ethnic and cultural diversity in Indonesia is an important social capital in national development, as values such as mutual cooperation (gotong royong), deliberation (deliberation), tolerance, and solidarity strengthen social cohesion, build social networks, and encourage community participation. This diversity enables cross-group cooperation that supports social, economic, and governance development. However, its utilization faces several obstacles, including horizontal conflict, a lack of multicultural education, the influence of globalization and modernization, and socio-economic disparities between groups. Therefore, managing diversity through multicultural education, intercultural dialogue, revitalizing local values, and inclusive policies is key to transforming ethnic and cultural diversity into a strategic asset in strengthening solidarity, building national character, and promoting sustainable national development.